Deep seabed mining in international waters - Diora Ziyaeva; Cody Anthony (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
The International Seabed Authority recently concluded its yearly meeting without finalizing a formal Mining Code for the deep seabed. This Perspective considers the impact of the lack of a Mining Code and provides recommendations for developing countries seeking to conduct deep sea mining projects.
Keywords: 330